2004
DOI: 10.1021/ja0445847
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Strong Two-Photon Absorption in π-Conjugated Porphyrin Dimers via Double-Resonance Enhancement in a Three-Level Model

Abstract: We present the two-photon absorption (2PA) spectra of a series of conjugated porphyrin dimers and show that they possess extremely large intrinsic (femtosecond) peak 2PA cross sections, up to sigma2 = 1 x 104 GM in the near-IR region; these are among the highest values measured for any organic molecule. Moreover, we demonstrate that the second-order perturbation theory applied to a simple three-level model gives a perfect quantitative description of the observed 2PA cross section. By comparing all the factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 272 publications
(231 citation statements)
references
References 22 publications
11
216
0
4
Order By: Relevance
“…Porphyrin derivatives are often effective PDT agents, as exemplified by verteporfin and Photofrin 4 . Recently it has been found that the two-photon cross-section of a porphyrin can be increased 500-fold by forming a conjugated porphyrin dimer [19][20][21] , and that these dimers have high singlet oxygen yields 20,22 . Here we show that porphyrin dimers can be functionalised with polar substituents to give effective TPE-PDT drugs.…”
mentioning
confidence: 99%
“…Porphyrin derivatives are often effective PDT agents, as exemplified by verteporfin and Photofrin 4 . Recently it has been found that the two-photon cross-section of a porphyrin can be increased 500-fold by forming a conjugated porphyrin dimer [19][20][21] , and that these dimers have high singlet oxygen yields 20,22 . Here we show that porphyrin dimers can be functionalised with polar substituents to give effective TPE-PDT drugs.…”
mentioning
confidence: 99%
“…Porphyrin dimers were previously shown to possess one of the highest two‐photon absorption (TPA) cross‐sections, which makes them desirable sensors for use with two‐photon excitation 29, 32, 33. One of the reasons for these exceptionally high values of TPA cross‐sections is the efficient conjugation over the whole length of the molecule 34, 35.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48][49][50][51] Conjugated porphyrin dimers exhibit much larger third-order susceptibilities (g) than the corresponding porphyrin monomers, [49][50][51] thus Equation (3) implies that dimeric analogues of JR1 will display even higher sensitivities to electric field. Previous studies on voltagesensitive SHG dyes have focused entirely on styryl and retinal chromophores.…”
Section: Methodsmentioning
confidence: 99%